2014
DOI: 10.1016/j.bpobgyn.2014.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Male contraception

Abstract: Clear evidence shows that many men and women would welcome new male methods of contraception, but none have become available. The hormonal approach is based on suppression of gonadotropins and thus of testicular function and spermatogenesis, and has been investigated for several decades. This approach can achieve sufficient suppression of spermatogenesis for effective contraception in most men, but not all; the basis for these men responding insufficiently is unclear. Alternatively, the nonhormonal approach is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 64 publications
0
32
0
Order By: Relevance
“…It is important to note that the vas deferens has been known to regenerate, in order to fully prevent the fallopian tubes need to be cauterized (burned) using electricity (Pollard, 2011). The failure rate is less than one percent but requires several months to achieve full contraceptive efficiency (Chao, Page, & Anderson, 2014). It should also be noted that reversal of the procedure can be costly and unreliable (Chao, Page, & Anderson, 2014).…”
Section: Permanent Birth Control Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that the vas deferens has been known to regenerate, in order to fully prevent the fallopian tubes need to be cauterized (burned) using electricity (Pollard, 2011). The failure rate is less than one percent but requires several months to achieve full contraceptive efficiency (Chao, Page, & Anderson, 2014). It should also be noted that reversal of the procedure can be costly and unreliable (Chao, Page, & Anderson, 2014).…”
Section: Permanent Birth Control Methodsmentioning
confidence: 99%
“…The failure rate is less than one percent but requires several months to achieve full contraceptive efficiency (Chao, Page, & Anderson, 2014). It should also be noted that reversal of the procedure can be costly and unreliable (Chao, Page, & Anderson, 2014).…”
Section: Permanent Birth Control Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no effective, reversible, and safe contraception option for men. Hormonal male contraception inhibits the hypothalamic–pituitary–gonadal axis via exogenous sex hormones to suppress endogenous testosterone (T) production, intratesticular T concentrations, and spermatogenesis while providing sufficient systemic androgens to preserve normal functions (Chao et al ., ; Wang et al ., ). With T alone, prior studies demonstrated that spermatogenesis suppression is not uniform in all men; some men did not fully respond to the dose used or escaped from suppression, despite the use of supraphysiologic doses of T (World Health Organization Task Force on Methods for the Regulation of Male Fertility, ; World Health Organization Task Force on the Regulation of Male Fertility, ; Gu et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Allowing both men and women to share family planning responsibilities by increasing contraceptive choices would promote important, but still largely unmet individual and societal needs, such as ameliorating the number of elective terminations for unplanned pregnancies and reducing overpopulation 2 . Promising candidate non-hormonal male-directed approaches have been identified 3,4 , but pivotal trials in humans that would be necessary for drug or device registration are lacking: table 1. In contrast, more than 2000 men have already been exposed to over 2000 person-years of male hormonal contraception (MHC, consisting of androgens with or without progestins) to assess contraceptive efficacy: table 2.…”
Section: Introductionmentioning
confidence: 99%